Quo Vadis Pengecualian Kebijakan Dari Objek Gugatan di Pengadilan Tata Usaha Negara di Era Pandemi Covid-19 - Ubaiyana, Ubaiyana; Falah, Fajrul (Fakultas Syariah, 2021)
Abstract: The issuance of Perppu Number 1 of 2020 in the midst of the Covid-19 pandemic, has invited a number of controversies. One of the articles that also received criticism was Article 27 paragraph (3). Article a quo negates every action, including decisions, is not the object of the PTUN lawsuit. This is clearly contrary to the principle of the rule of law which guarantees the protection of the law and human rights. PTUN is one of the means of legal protection and human rights for people who are harmed by decisions or actions of state administration. By examining library materials or secondary data and using legislation, concepts, and historical approaches, this article will focus on two problem formulations, namely whether all actions and decisions according to the Perppu are included in the object of the PTUN lawsuit? and why are these actions and decisions excluded from the object of the Administrative Court lawsuit? After conducting an in-depth investigation, the actions and decisions based on the Perppu are indeed the objects of the PTUN lawsuit, but theoretically-juridically the exceptions from the object of the lawsuit mandated by the Perppu are justified.Keywords: Policy; lawsuit; covid-19Abstrak: Lahirnya Perppu Nomor 1 Tahun 2020 di tengah pandemi Covid-19, mengundang sejumlah kontroversi. Salah satu pasal yang turut mendapat kecaman adalah Pasal 27 ayat (3). Pasal a quo menegaskan setiap tindakan termasuk keputusan bukan merupakan objek gugatan Peradilan Tata Usaha Negara (PTUN). Hal ini jelas bertentangan dengan prinsip negara hukum yang menjamin perlindungan hukum dan hak asasi manusia. PTUN menjadi salah satu sarana perlindungan hukum dan hak asasi manusia bagi masyarakat yang dirugikan akibat keputusan atau tindakan administrasi negara. Penelitian ini bertujuan menganalisis tindakan dan keputusan yang dapat dikecualikan dari objek gugatan kepada PTUN adalah yang berkaitan dengan penanganan pandemi Covid-19. Dengan meneliti bahan pustaka atau data sekunder, serta menggunakan pendekatan perundang-undangan, konsep, dan sejarah, artikel ini berfokus pada dua rumusan masalah yaitu apakah segala kebijakan dan keputusan menurut Perppu termasuk dalam objek gugatan PTUN? dan mengapa tindakan dan keputusan tersebut dikecualikan dari objek gugatan PTUN? Setelah melakukan penelusuran mendalam, tindakan dan keputusan berdasarkan Perppu memang merupakan objek gugatan PTUN, namun secara teoritis-yuridis pengecualian dari objek gugatan yang diamanatkan Perppu dibenarkan keberadaannya.Â Â Kata Kunci: kebijakan; gugatan, covid-19.